The effect of oral administration of NXP032 equivalent to intraperitoneal administration in an Alzheimer’s disease model - Lee, Jae Min; Choi, You Jung; Sung, Da-Eun; Sim, Tae Hyeok; Kim, So Hee; Yeo, Seung Geun; Kim, Youn-Jung (Frontiers in Pharmacology, 2025)
IntroductionAlzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by cognitive impairment, amyloid beta (Aβ) plaque accumulation, neuroinflammation, and neurodegeneration. Excessive oxidative stress exacerbates these pathologies, potentially accelerating disease progression. Although antioxidants like vitamin C can mitigate neuroinflammation and offer neuroprotective effects, their efficacy is often limited due to rapid oxidation, particularly when administered orally. NXP032 has been developed to stabilize vitamin C and sustain its antioxidant effects over time.MethodsThis study evaluated the effects of NXP032 administered orally (PO) and intraperitoneally (IP) on AD pathology, specifically focusing on Aβ accumulation and neuroinflammation, using the 5xFAD mouse model over an 8-week period.ResultsBoth IP and PO administration of NXP032 significantly reduced Aβ plaque accumulation and thioflavin-S staining, while attenuating neuroinflammation in 5xFAD mice. This was associated with decreased neurodegeneration, evidenced by reduced Fluoro-Jade C staining in the hippocampus. Additionally, both administration routes resulted in significant cognitive function improvements. DiscussionNXP032 demonstrates potential as a therapeutic strategy to address multiple aspects of AD pathology and slow disease progression. The efficacy of oral administration is particularly notable, offering a practical method for clinical application.